Odpowiedzi

2010-01-18T17:58:56+01:00
C)0,7x + 5z + 0,002y - 4,05z + 1,4x = 2,1x + 0,002y + 0,95z

d)9m + 7n - 6k +4 - 2m + 6n +2,5 = 6k + 7m + 13n +6,5

e)1,05s + 2,94y - 0,09s + 7,06y + 2,04s = 3,18s + 10y

f) 0,8a + 1,2a + 0,4b - 2a - 0,4b = 0 (bo wszystkie wyrazy się zredukują =)
1 5 1
2010-01-18T17:59:14+01:00
C)0,7x + 5z + 0,002y - 4,05z + 1,4x=2,1x+0,95x+ 0,002y
d)9m + 7n - 6k +4 - 2m + 6n +2,5=7m+13n- 6k+6,5
e)1,05s + 2,94y - 0,09s + 7,06y + 2,04s=3s+10y
f) 0,8a + 1,2a + 0,4b - 2a - 0,4b=0
1 5 1
2010-01-18T18:03:44+01:00
C) 2,1x+1,05z+0,002y
d)7m+13n+7,5-6k
e)3s+10
f)0